The Utilization of Chitosan from Maggot (Hermetia illucens) Exuvia as Edible Coating for Tomatoes (Lycopersicon esculentum) and Edible Film with the Addition of Honey as an Antibacterial Agent - Daniel; Sitorus, Saibun; Pasaribu, Subur P.; Marliana, Eva; Hairani, Rita; Ruga, Ritbey; Purba, Ritson; Saleh, Chairul; Pratiwi, Djihan Ryn; Magdaleni, Agustina Rahayu; Masmur, Indra; Masmur, Hestina (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
The use of chitosan from maggot (Hermetia illucens) exuvia as an edible coating for tomatoes (Lycopersicon esculentum) and an edible film with honey added as an antibacterial agent was investigated. This study aimed to determine the yield of chitosan from black soldier fly (BSF, Hermetia illucens) maggot exuviae as an edible coating. The chitosan was produced from chitin by deacetylation, and its effect on the weight loss and vitamin C levels of tomatoes for 7 days after treatment was investigated. The chitosan coating was characterized by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy. The antibacterial activity was evaluated using a disk diffusion method. The result showed that by deacetylation, conversion of chitin produced chitosan with a yield of 72% and a deacetylation degree of 75.05%. The chitosan coating significantly affected the weight loss of tomatoes, with the best concentration being 2%. However, the treatment did not significantly affect the decrease in vitamin C levels. The edible chitosan film from BSF maggot exuviae with added honey had a thickness, water content, and water vapor transmission rate of 0.156 mm, 16.9913%, and 30.45 g/m2/24 hours, respectively. SEM characterization showed a relatively dense surface structure, which was slightly smooth and porous. Regarding antibacterial activity, the edible chitosan film inhibited Staphylococcus aureus with an inhibition zone of 10.37 mm; however, Escherichia coli was not inhibited. These results suggest that chitosan from BSF maggot exuviae has potential as an effective edible coating for reducing weight loss in tomatoes despite showing limited antibacterial properties.